2015
DOI: 10.1016/j.wneu.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, Surgical Treatment, and Cure for SUNCT Syndrome

Abstract: Microvascular decompression provides an appropriate therapeutic choice if vascular compression of the trigeminal nerve is identified. From our 2 cases, we propose that, in some cases of SUNCT diagnosed previously, characteristic symptoms were induced by compression of the side surface of the first branch of the trigeminal nerve at the root exit zone by the intracranial artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…We summarized 69 cases of SUNCT-like conditions associated with certain etiologies in 62 English-language studies reported on from 1991 to 2017 and for which there were detailed descriptions of the clinical features and imaging results of the patients. These cases comprised 17 with neoplasm, 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 35 with neurovascular disease, 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 2 with trauma, 44 45 10 with infection, 46 47 48 49 50 51 52 53 54 3 with inflammatory disease, 55 56 57 and 2 with congenital malformation ( Table 1 , 2 , and 3 ). 58 59 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We summarized 69 cases of SUNCT-like conditions associated with certain etiologies in 62 English-language studies reported on from 1991 to 2017 and for which there were detailed descriptions of the clinical features and imaging results of the patients. These cases comprised 17 with neoplasm, 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 35 with neurovascular disease, 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 2 with trauma, 44 45 10 with infection, 46 47 48 49 50 51 52 53 54 3 with inflammatory disease, 55 56 57 and 2 with congenital malformation ( Table 1 , 2 , and 3 ). 58 59 …”
Section: Resultsmentioning
confidence: 99%
“…Thirty cases were caused by neurovascular compression, 19 20 22 24 25 26 27 28 30 31 32 33 34 35 36 39 40 41 42 43 four cases were due to cerebral infarction, 23 29 37 38 and one case was due to cavernous angioma. 21 MRI findings showed that 32 cases were at the pons level, including a case of left cerebellar infarction, while its ischemic penumbra was considered to involve the ascending spinothalamic tract and descending trigeminal fibers at or below their site of entry (and subsequent caudal passage) into the lateral pontine tegmentum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurovascular compression has been considered a distinguishing feature from trigeminal neuralgia, due to a reduced prevalence in SUNCT (5). Notwithstanding, there are some reports of trigeminal compression by vascular loops in SUNCT patients who went into remission after microvascular decompression surgery (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a subset of patients with SUNHA and documented neurovascular conflict with the trigeminal nerve, 15 of 23 reported patients undergoing microvascular decompression (MVD) experienced complete resolution of pain (7,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%